Effectiveness of an experimental program for the technical and technical-tactical training of female boxers (using the example of uppercuts) - Chernokolenko , Anastasiia (Sportyvnyi Visnyk Prydniprovia, 2024)
At the stages of initial and preliminary basic training, a fundamental base of technical and technical-tactical preparedness is laid for female athletes who engage in boxing, which is related to the formation of skills and abilities of all types of blows and defense against them. However, the issue of control over these types of training remains out of consideration, since it is not provided for in the program of the Children’s-Youth Sports Schools, Specialized Children’s-Youth Schools of the Olympic Reserve and Schools of Higher Sports Mastery (2009). The relevance of the research is to determine the effectiveness of the experimental program on the level of technical and technical-tactical preparedness for performing blows from below and protecting against them at the general group, intragroup and individual levels, to develop evaluation criteria on a 5-level scale. The aim of the study: to determine the effectiveness of the experimental program implemented in the educational and training process to improve the technical and technical-tactical training of female athletes engaged in boxing at the stage of preliminary basic training (using the example of blows from below and protection against them). Material and methods: theoretical analysis and generalization of scientific and methodological literature, analysis of programmatic and normative documents, pedagogical observation, control testing, methods of mathematical statistics. 13-14-year-old girls who are engaged in boxing at the stage of preliminary basic training of the second year of training took part in the pedagogical experiment. Athletes were formed into two groups: the main group included 15 athletes, the control group – 16 athletes. Control testing was carried out at the end of the annual cycle of training according to control tests, which were determined as a result of expert evaluation by boxing coaches. The results. The results of the control testing show that the level of technical and technical-tactical preparedness of the technique of performing blows from below and defending against them at the general group level is at the “average” level, at the intragroup level in the main group – at the “average” level, and in the control group – at “below average” levels, at the individual level the «average» level prevails in the main group, and the “below average” and “average” levels prevail in the control group. Conclusions. The analysis of scientific and methodical literature, the training program of Children’s-Youth Sports Schools, Specialized Children’s-Youth Schools of the Olympic Reserve and Schools of Higher Sports Mastery in boxing and practical experience shows that in the process of learning blows from below is the most difficult from the point of view of the biomechanical structure of execution. The results of the control testing provide grounds for asserting that the implemented experimental program is effective, as significant differences between the main and control groups were determined at p≤0.01.